Efficacy of narrowband ultraviolet B therapy in pityriasis lichenoides [Pitriyazis likenoideste dar bant ultraviyole B tedavisinin etkinliǧi] - (:unkn) unknown (My University, 2011)
Objective: Pityriasis lichenoides is a papulosquamous inflammatory skin disease. Narrowband ultraviolet B, a commonly used phototherapeutic modality, has an important place in its treatment. Treatment and follow-up results of pityriasis lichenoides patients treated with narrowband ultraviolet B in our phototherapy unit are presented here. Methods: The treatment records of 25 pityriasis lichenoides patients who completed narrowband ultraviolet B treatment were retrospectively evaluated. Ultraviolet B treatment was performed 3 days a week until complete resolution or minimal residual activity was achieved. Treatment response was determined as complete, marked, moderate or mild improvement or as no response. The appearance of new skin lesions during the follow-up period after treatment was defined as a relapse. Results: The mean age of the patients was 22 (minmax: 3-49) and the mean disease duration was 30.2(min-max:3-120) months. After a mean of 24.6 (minmax: 12-45) treatment sessions, 17 patients (68%) achieved complete, 4 patients (16%) marked, 1 patient moderate (4%) and 1 patient (4%) mild improvement whereas 2 patients (8%) showed no response. Eight patients (32%) had mild to moderate erythema at leastonce during the treatment. None of the patients gave up treatment due to side effects. In all 9 patients who werefollowed up, relapse was seen after a mean time of 10.1 months (min-max 1- 24 months). Conclusion: The results of the present study show that narrowband ultraviolet B is an effective and safe method in the treatment of pityriasis lichenoides.
Keywords: Narrowband ultraviolet B; Phototherapy; Pityriasis lichenoides